The significance ascribed to contacting a diaconal suicide-prevention crisis line in Norway: a qualitative study - Vattø, Ingvild E. (Mental health, religion & culture, 2020)
Suicide-prevention crisis lines worldwide offer support to individuals in crisis, nonetheless, there is limited in-depth knowledge as to the significance of contacting these services from the service-users’ first-hand perspectives. This study aimed to provide a deeper understanding of the significance ascribed to contacting a diaconal suicide-prevention crisis line in Norway. In-depth qualitative interviews were conducted with nine callers. The material was analysed using systematic text condensation. The analysis revealed three main themes reflecting the crisis line’s emotional, relational and existential support functions in terms of providing: (i) immediate emotional availability, (ii) experiences of connectedness and acceptance, and (iii) a safe space for existential meaning-making processes. The findings point to the need for future research on the value of integrating biopsychosocio-existential perspectives into intervention models within the field of crisis support.